Pengembangan Instrumen Keterlibatan Orangtua Dalam Menumbuhkan Minat Baca - Purwandari, Septiyati; Triana, Putri Meinita; Husna, Aftina Nurul; Mayawati, Annis Ika (Universitas Muhammadiyah Magelang, 2020)
The considerations for this research are (1) growing interest in reading is the duty of parents, but what forms of parental involvement are not widely understood. (2) the dynamics of the problem of parenting skills are very interesting, progressive and urgent to continue to be studied because the acceleration of the digital era requires parents to be more responsive and literate (3) there are still few studies that discuss the development of parental involvement instruments in fostering reading interest both quantitatively and qualitatively. So that developing an instrument that can provide information on the extent of parental involvement in fostering reading interest is the aim of this study. The research stages are carried out by (1) affirming the measuring area; (2) writing items; (3) testing; and (4) psychometric analysis using quantitative methods. Therefore, this research instrument uses a questionnaire prepared based on the literature review process that supports the research variables. Furthermore, the questionnaire is tested for content validity by an expert (Expert Judgment) to conduct a study and selection of items for each indicator. In this process, 40 items from 82 items were selected, as a result of this study. The trial was carried out on the research subjects, namely parents who have children aged from early childhood to elementary school with a total of 521 respondents. While the reliability test of this questionnaire shows the Cronbach Alpha coefficient = 0.941, which means that in psychomoteric analysis this instrument has perfect internal consistency. Based on these data, it can be concluded that the instrument developed can measure the extent to which parents are involved in fostering children's reading interest.